2021
DOI: 10.3390/microorganisms9122564
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Salmonella enterica Virulence and Host Pathogenesis through Targeting sdiA by Using the CRISPR-Cas9 System

Abstract: Salmonella enterica is a common cause of many enteric infections worldwide and is successfully engineered to deliver heterologous antigens to be used as vaccines. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs) RNA-guided Cas9 endonuclease is a promising genome editing tool. In the current study, a CRISPR-Cas9 system was used to target S.enterica sdiA that encodes signal molecule receptor SdiA and responds to the quorum sensing (QS) signaling compounds N-acylhomoserine lactones (AHLs). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…This was highly reasoned since hydrophobic interactions were almost conserved for all docked ligands, while more extended hydrophilic networks were depicted with similar ligands binding at the QscR active site. This QscR-specific preferentiality towards polar-directed bindings was also consistent across several reported studies [ 40 , 54 ]. Docking studies further signified the ligand’s preferential binding to particular residues (Ser38), which was also reported as vital for defining the QscR signal specificity through guided preferential binding of native 3-O-HSL over the native unsubstituted ligands [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…This was highly reasoned since hydrophobic interactions were almost conserved for all docked ligands, while more extended hydrophilic networks were depicted with similar ligands binding at the QscR active site. This QscR-specific preferentiality towards polar-directed bindings was also consistent across several reported studies [ 40 , 54 ]. Docking studies further signified the ligand’s preferential binding to particular residues (Ser38), which was also reported as vital for defining the QscR signal specificity through guided preferential binding of native 3-O-HSL over the native unsubstituted ligands [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on such docking behavior, it was suggested that polar-directed binding has a significant impact on the ligand/pocket accommodation at different QS proteins. The latter pocket structures differences and their impact on ligand binding were also highlighted by Lintz et al where they investigated the comparative architectures of the ligand-binding domains and AHL-related binding pockets of several QS including CviR, QscR, LasR, TraR, and SdiA [24,56].…”
Section: Discussionmentioning
confidence: 85%
“…The functionality of quorum-sensing systems resides on basic components that are druggable and tend to be absent in mammals ( LaSarre and Federle, 2013 ; Fleitas Martínez et al, 2019b ; Ellermann and Sperandio, 2020 ). Similarly to the observed in bacterial secretion systems, mutant strains in quorum sensing system components could become avirulent strains in infection models ( Askoura et al, 2021 ; Kumar et al, 2021 ). Studies focused on quenching quorum sensing systems with inhibitors have demonstrated that targeting these communication systems is a promising strategy to face resistant pathogens ( Sully et al, 2014 ; Daly et al, 2015 ; Parlet et al, 2019 ; Salam et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%